THE ROLE OF NATIONAL VALUES IN THE STABILITY OF MARRIAGE AND FAMILY IN MODERN UZBEK FAMILIES (Academicia Globe: Inderscience Research, 2021)
The Uzbek people pay special attention to the spirituality of the family, the sacred duty of every modern family is to educate young people who meet the requirements of today's independent republic, using the spiritual heritage.